2011
DOI: 10.1111/j.1469-0691.2010.03317.x
|View full text |Cite
|
Sign up to set email alerts
|

Stationary biofilm growth normalizes mutation frequencies and mutant prevention concentrations in Pseudomonas aeruginosa from cystic fibrosis patients

Abstract: Bacterial biofilms play an important role in the persistent colonization of the respiratory tract in cystic fibrosis (CF) patients. The trade-offs among planktonic or sessile modes of growth, mutation frequency, antibiotic susceptibility and mutant prevention concentrations (MPCs) were studied in a well-defined collection of 42 CF Pseudomonas aeruginosa isolates. MICs of ciprofloxacin, tobramycin, imipenem and ceftazidime increased in the biofilm mode of growth, but not the MPCs of the same drugs. The mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Interestingly, Garcia‐Castillo et al . () have reported that biofilm populations of CF isolates showed a lower mutation frequency compared to planktonic cultures. In contrast, Conibear et al .…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, Garcia‐Castillo et al . () have reported that biofilm populations of CF isolates showed a lower mutation frequency compared to planktonic cultures. In contrast, Conibear et al .…”
Section: Discussionmentioning
confidence: 97%
“…Excluding the 1973 isolates from the calculation, we find the mutation rate to be 6.9 × 10 −11 SNPs/bp per generation. It is important to note that these estimates show no indication of increased rates of mutation, as has been suggested for biofilm-associated cells and CF infection-associated cells due to oxidative stress or other phenomena (28)(29)(30)(31)(32).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, horizontal gene exchange is enhanced in biofilms. Whereas the mutation frequency is usually stable over time in bacteria, an increased value of this parameter has been demonstrated in bacteria growing in biofilms (Molin & Tolker‐Nielsen, 2003; Driffield et al , 2008; García‐Castillo et al , 2011). So‐called hypermutators (=mutators) have a spontaneous mutation rate that is 10–1000 times higher than that of a wild‐type strain.…”
Section: Emergence Of Antimicrobial Resistance In Biofilms and The Comentioning
confidence: 99%